Implementasi Akad Dalam Perbankan Syariah Di Indonesia - Hasan Sultoni; Ayu Rahmawati; Filda Ashofa (xxxx-xxxx, 2022)
The contract is the most important element that must be considered in the transaction because the contract that determines a transaction is declared valid according to the syara' or canceled, so that the contract must be considered from various aspects both from the pillars and conditions, the object of the contract, as well as the one who terminates the contract. Contracts are divided into two types, namely exchange contracts and mix contracts. Implementation of the contract has become the operational basis in Islamic Financial Institutions today including Islamic Banking. The contract that underlies every business transaction, with the contract will know someone's motivation in carrying out business transactions and find out the extent to which business transactions are carried out based on syara' and how the contract is implemented in Islamic financial institutions including Islamic banking.